Delay-tolerant distributed space-time coding with feedback for cooperative MIMO relaying systems - Peng, Tong; de Lamare, Rodrigo C. (EURASIP journal on wireless communications and networking, 2018)
An adaptive delay-tolerant distributed space-time coding (DSTC) scheme equipped with a feedback channel is proposed for two-hop cooperative multiple-input multiple-output (MIMO) networks. A maximum likelihood receiver and adjustable code matrices subject to a power constraint with a decode-and-forward cooperation strategy are considered with different DSTC antenna configurations. In the proposed delay-tolerant DSTC schemes, an adjustable code matrix is employed to transform the space-time coded matrices at the relay nodes. Stochastic gradient and least squares algorithms are also developed with reduced computational complexity. The proposed algorithms are then extended to a cooperative MIMO system using amplify-and-forward strategy and opportunistic relaying algorithms in order to develop a delay-tolerant coding scheme combined with optimal relay selection strategies. An upper bound on the pairwise error probability and a rank criterion analysis are derived which indicate the advantage of the proposed algorithms. Simulation results show that the proposed algorithms obtain significant performance gains and address the delay issue in cooperative MIMO systems as compared to existing DSTC schemes.